ANALISIS KUALITAS PELAYANAN DAN RESPONSIVENESS TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA PT INFINITI MARINE - Devin, Devin; Pranoto, Suryo Budi (SCIENTIA JOURNAL, 2019)
When talking about world economy, it will not be separated from trading activities. Trading activities are increasingly not only in country, but have expanded between countries. Exports and imports support the implementation of trade between countries. The freight forwarding business growing rapidly in Indonesia. Companies must able to determine the right marketing strategy, in order to survive and win the competition. To be able to continue survive, the company must be able to know what is needed or expected by its customers. Many factors are consider by consumers before using a service. This research was conducted with the aim to analyze service quality and responsiveness to customer satisfaction in using the services of PT Infiniti Marine. Data collection techniques by distributing questionnaires to 175 respondents who were the samples in this study. Respondents in this study were the customers of PT Infiniti Marine. Data analysis used multiple linear regression analysis with the help of SPSS version 21 software. The results of the research test showed that service quality and responsiveness had a simultaneous effect on customer satisfaction in using the services of PT Infiniti Marine. This indicates that the better the quality of service and responsiveness, customer satisfaction will increase.